Resistin Expression Is Associated With Interstitial Lung Disease in Dermatomyositis - Ye, Lifang; Zuo, Yu; Chen, Fang; Xu, Yuetong; Zhang, Puli; Yang, Hongxia; Lin, Sang; Peng, Qinglin; Wang, Guochun; Shu, Xiaoming (Frontiers in Medicine, 2022)
Objective In the current study, we aimed to assess resistin mRNA levels in the peripheral blood mononuclear cells (PBMCs) of patients with dermatomyositis-related interstitial lung disease (DM-ILD) and their correlation with disease activity. Methods We detected resistin mRNA levels in the PBMCs of 37 patients with DM-ILD and 19 healthy control subjects by performing quantitative reverse transcription real-time polymerase chain reaction analysis. Associations between resistin expression levels and major clinical manifestations, laboratory examinations, and disease activity were also analyzed. In addition, resistin expression in lung specimens from patients with DM-ILD was examined via immunohistochemistry. Results Resistin mRNA levels in PBMCs were significantly higher in patients with DM-ILD (p = 0.014). Among these patients, the resistin levels were significantly elevated in those with rapidly progressive ILD than in those with chronic ILD (p = 0.012). The resistin mRNA levels in DM-ILD positively correlated with serum alanine aminotransferase (r = 0.476, p = 0.003), aspartate aminotransferase (r = 0.488, p = 0.002), lactate dehydrogenase (r = 0.397, p = 0.014), C-reactive protein (r = 0.423, p = 0.008), ferritin (r = 0.468, p = 0.003), carcinoembryonic antigen (r = 0.416, p= 0.011), carbohydrate antigen 125 (r = 0.332, p = 0.047), interleukin-18 (r = 0.600, P < 0.001), and lung visual analog scale values (r = 0.326, p = 0.048), but negatively correlated with the percent predicted carbon monoxide-diffusion capacity (r = -0.447, p = 0.041). Immunohistochemical analysis of resistin confirmed its elevated expression in the macrophages, alveolar epithelial cells, and weak fibrotic lesions from patients with DM-ILD. Conclusions Resistin levels were increased in patients with DM-ILD and associated with disease activity and ILD severity. Therefore, resistin may participate in the pathogenesis of DM-ILD and may act as a useful biomarker.